2016
DOI: 10.1007/s10551-016-3224-5
|View full text |Cite
|
Sign up to set email alerts
|

Leader Narcissism Predicts Malicious Envy and Supervisor-Targeted Counterproductive Work Behavior: Evidence from Field and Experimental Research

Abstract: Building on the emotion-centered model of voluntary work behavior, this research tests the relations between leader narcissism, followers' malicious and benign envy, and supervisor-targeted counterproductive work behavior (CWB). Results across five studies (i.e., one pilot study (N = 50), two experimental studies (N = 74 and 50), and two field surveys (N = 365 and 100) indicate that leader narcissism relates positively to followers' negative emotions (i.e., malicious envy), which in turn mediates the positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(121 citation statements)
references
References 94 publications
(146 reference statements)
3
115
2
1
Order By: Relevance
“…Lange, 2016) and uncooperative decisions (Parks, Rumble, & Posey, 2002), and other works have demonstrated that envy-related behaviors, such as counterproductive work behavior, were correlated with malicious thoughts and intentions (e.g. Braun, Aydin, Frey, & Peus, 2018). In the current work we continue to develop and merge these lines of research.…”
Section: Introductionmentioning
confidence: 92%
“…Lange, 2016) and uncooperative decisions (Parks, Rumble, & Posey, 2002), and other works have demonstrated that envy-related behaviors, such as counterproductive work behavior, were correlated with malicious thoughts and intentions (e.g. Braun, Aydin, Frey, & Peus, 2018). In the current work we continue to develop and merge these lines of research.…”
Section: Introductionmentioning
confidence: 92%
“…The dark triad term used by Paulhus and Williams 34 refers to narcissism, psychopathy and Machiavellianism. Narcissist individuals describe as a complex personality pattern characterized by feelings of dominance, superiority, exploitation and entitlement 44,45 . They overlap conceptually and empirically with a grandiose sense of self‐importance, impulsiveness and self‐esteem because counterproductive work behaviors often constitute specific instances of impulsive behaviors.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…For example, the research linking narcissism to counterproductive work behaviors (absenteeism, sabotage, aggression toward others) is robust (Grijalva & Newman, 2015;O'Boyle et al, 2012;Penney & Spector, 2002). Abusive supervision, as often manifest by narcissists, has been shown to be a significant cause of employee stress and health concerns (e.g., Braun, Aydin, Frey, & Peus, 2015;Thompson, 2011). Other research has shown that those high in narcissism also have a greater likelihood of engaging in sexual harassment (e.g., Blinkhorn, Lyons, & Almond, 2015;Mumford, Connelly, Helton, Strange, & Osburn, 2001;Zeigler-Hill et al, 2016) or having similar personality profiles to psychopaths and white collar criminals (Blickle et al, 2006;Paulhus & Williams, 2002;Rauthmann, 2012).…”
Section: Study Implicationsmentioning
confidence: 99%